Crafting Humorous Soft Toys: Incorporating Humour to a Holistic Craft Process in Early Years Education - Rönkkö, Marja-Leena; Aerila, Juli-Anna; Stenius, Tuula (Design and Technology Education: An International Journal, 2025)
This study explores humour’s role in a holistic craft process when 7–8-year-olds design personalised soft toys. Humour enhances learning environments by fostering joy, belonging and a positive atmosphere, acting as a motivational tool in experiential and arts-based learning. The study aims to answer the following questions: (1) What are the humorous characteristics of the soft toys created by the pupils? (2) How does the crafting of humorous soft toys proceed? Employing an educational design research methodology, the project involved 36 first-grade pupils from an urban Finnish school over a 10-day intervention. The study examines how humour, when integrated into a holistic craft process, supports the making and designing of soft toys. In the study, the pupils created humorous soft toys, often anthropomorphised with exaggerated or contradictory traits. Challenges emerged in translating 2D drawings into 3D soft toys, particularly with sewing and fabric painting. Nevertheless, the final products were unique and evoked positive emotions. The findings suggest that incorporating familiar elements, such as humour and soft toys, into the holistic craft process in early years education can enhance motivation and learning outcomes, thus supporting the integration of humour into educational contexts to foster creativity and emotional expression.